TLR2 Deficiency Exacerbates Imiquimod-Induced Psoriasis-Like Skin Inflammation through Decrease in Regulatory T Cells and Impaired IL-10 Production - Nakao, Momoko (Int J Mol Sci, 2020)
Emerging evidence has demonstrated that Toll-like receptors (TLRs) are associated with autoimmune diseases. In this study, we investigated the role of TLR2 in psoriasis using imiquimod-induced psoriasis-like dermatitis. Although TLR2 signaling is known to play a critical role in the induction of proinflammatory cytokines by immune cells, such as dendritic cells (DCs), macrophages, and monocytes, TLR2 deficiency unexpectedly exacerbated psoriasiform skin inflammation. Importantly, messenger RNA (mRNA) levels of Foxp-3 and IL-10 in the lesional skin were significantly decreased in TLR2 KO mice compared with wild-type mice. Furthermore, flow cytometric analysis of the lymph nodes revealed that the frequency of regulatory T cells (Tregs) among CD4-positive cells was decreased. Notably, stimulation with Pam3CSK4 (TLR2/1 ligand) or Pam2CSK4 (TLR2/6 ligand) increased IL-10 production from Tregs and DCs and the proliferation of Tregs. Finally, adoptive transfer of Tregs from wild-type mice reduced imiquimod-induced skin inflammation in TLR2 KO mice. Taken together, our results suggest that TLR2 signaling directly enhances Treg proliferation and IL-10 production by Tregs and DCs, suppressing imiquimod-induced psoriasis-like skin inflammation. Enhancement of TLR2 signaling may be a new therapeutic strategy for psoriasis.